Transforming Drama Education Through Nearpod: Development of Interactive Teaching Materials for University Students - Hutagalung, Trisnawati; Abdurahman Adisaputera, Abdurahman; Tansliova, Lili; Simanungkalit, Kaleb E. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This research aims to develop Nearpod media-assisted teaching materials for Drama courses in the Indonesian Language and Literature Education Study Program, Faculty of Language and Arts, Universitas Negeri Medan. This research uses the Research and Development (R&D) method, carried out until the product revision stage after validation. The research population was all fourth-semester students who took the KDBK Drama Teaching course, with 156 students. The sample was selected purposively, namely one class of 37 students who took part in learning using Nearpod-based teaching materials. The results showed that expert validation gave a perfect percentage for content aspects (85.7%), presentation aspects (85.5%), linguistic aspects (85.8%), and design aspects (85.6%). In addition, the results showed that using Nearpod media-assisted teaching materials significantly improved student learning outcomes in drama learning. This finding indicates that Nearpod is an effective digital media in improving engagement and learning outcomes in literature education.